Melanogenesis enhancement of saturated fatty acid methyl esters in B16F10 melanoma cells - Chaikul P. (2017)
Four methyl esters including lauric acid methyl ester, myristic acid methyl ester, palmitic acid methyl ester and stearic acid methyl ester, were synthesized by the Fischer esterification reaction, purified by column chromatography and identified using Fourier transform infrared spectroscopy and gas chromatography-mass spectroscopy. The cell cytotoxicity and melanogenesis stimulation effects of all purified methyl esters were evaluated in B16F10 melanoma cells in comparing to their corresponding saturated fatty acids. For cell cytotoxicity by sulforhodamine B assay, all methyl esters, lauric acid and myristic acid at 2.5 to 50.0 μg/ml exhibited high cell viability ( > 80%), while palmitic acid and stearic acid at 25.0 and 50.0 μg/ml were moderate cytotoxic. In melanogenesis stimulation assay, myristic acid methyl ester at 50.0 μg/ml and myristic acid at 10.0 μg/ml exhibited the highest melanin content of 1.58, 1.40 and tyrosinase activity of 1.67, 1.17 folds of the control, respectively. Myristic acid methyl ester demonstrated the melanin stimulation almost equal to 10.0 μg/ml of theophylline, a positive control. Thus, myristic acid methyl ester may be a useful agent for development of a pigment-stimulating product. © 2012 American Scientific Publishers. All rights reserved.